2018
DOI: 10.1128/aac.00046-18
|View full text |Cite
|
Sign up to set email alerts
|

Retained Activity of an O25b-Specific Monoclonal Antibody against an Mcr-1-Producing Escherichia coli Sequence Type 131 Strain

Abstract: Plasmid-encoded colistin resistance is emerging among extraintestinal pathogenic Escherichia coli strains, including those of the epidemic clone sequence type 131 (ST131)-H30. Mcr-1 transfers a phosphoethanolamine to the lipid A portion of lipopolysaccharide (LPS), conferring resistance to polymyxins. We investigated whether this modification changed the activity of the monoclonal antibody ASN-4, specific to the O25b side chain of ST131 LPS. We confirmed that, unlike colistin, ASN-4 retained its bactericidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…This includes humanized monoclonal antibodies that have been previously shown to target the LPS O25b antigen that is associated with E. coli ST131-H30 182 . The expression of mcr-1 does not affect the binding of ASn-4 to the LPS's O-antigen and the integration of the complement membrane-attack complex (MAC) into the LPS-modified outer membrane 182 . This means the expression of mcr-1 in E. coli ST131-H30 does not affect the functionality of the human immune system, nor does it not aid the strain via immune evasion.…”
Section: Dobias Et Al (2017)mentioning
confidence: 99%
“…This includes humanized monoclonal antibodies that have been previously shown to target the LPS O25b antigen that is associated with E. coli ST131-H30 182 . The expression of mcr-1 does not affect the binding of ASn-4 to the LPS's O-antigen and the integration of the complement membrane-attack complex (MAC) into the LPS-modified outer membrane 182 . This means the expression of mcr-1 in E. coli ST131-H30 does not affect the functionality of the human immune system, nor does it not aid the strain via immune evasion.…”
Section: Dobias Et Al (2017)mentioning
confidence: 99%
“…It had been demonstrated that O25b-specific MAb ASN-4 retained its bactericidal activity against an MCR-1 -positive colistin-resistant ST131-H30 strain by three mechanisms of action that are opsonophagocytosis, endotoxin neutralization, and complement-mediated killing. Subsequently, LPS O-antigen-targeting antibodies are thought to be an alternative way of combating MDR infections, including the emerging MCR-1 -positive isolates [ 198 ]. The general mode of action of novel antibodies against bacteria is depicted in Figure 8 .…”
Section: Novel Antibodies Against Mdr Bacteriamentioning
confidence: 99%
“…Moreover mAbs offer advantages in terms of limitation of selective pressure and precise delivery through engineering [ 116 ]. Nonetheless, there is only one mAb (A1124) currently proposed to treat multidrug resistant ExPEC sequence type 131-H30 [ 117 ], whose activity was confirmed against a colistin-resistant strain [ 118 ]. Its specific action on the LPS O-antigen (O25b) of E. coli points out the importance of saccharide epitopes to elicit protective mAbs [ 119 ].…”
Section: State Of the Art Of Vaccines And Mabs To Tackle Pseudomonas Aeruginosa And Escherichia Colimentioning
confidence: 99%